The Necessity of a Systematic Approach for the Use of MSCs in the Clinical Setting - Christophe Michel Raynaud; Arash Rafii (Stem Cells International)
Cell therapy has emerged as a potential therapeutic strategy in regenerative disease. Among different cell types, mesenchymal stem/stromal cells have been wildly studied in vitro, in vivo in animal models and even used in clinical trials. However, while clinical applications continue to increase markedly, the understanding of their physiological properties and interactions raises many questions and drives the necessity of more caution and supervised strategy in their use.